African Americans and Activism - Tangela Roberts (Journal for Social Action in Counseling and Psychology)
This study aimed to investigate the relationship between psychological well-being and PTSD symptoms in relation to activism orientations among African Americans. Additionally, the study explored the moderating roles of activist self-identity and length of activism involvement in these relationships. A national sample of 298 African American adults was examined, and the following findings were observed: African Americans with a greater inclination toward conventional activism reported higher levels of psychological well-being. Those who self-identified as activists displayed a nearly fourfold decrease in PTSD symptoms. Moreover, older African Americans showed decreased PTSD symptoms and increased psychological well-being compared to younger adults, while African American females reported higher levels of psychological well-being compared to males. Neither high-risk activist orientation nor activist self-identification significantly contributed to the prediction of PTSD symptoms or psychological well-being. Additionally, African American females and older adults with longer durations of involvement in activist organizations reported higher levels of psychological well-being. These findings emphasize the importance of considering age, sex, and duration of activist involvement as contributing factors in understanding variations in mental health. The clinical and community implications of these findings are further discussed.